How age-inclusive human resource practices relate to career sustainability: the role of work-family enrichment and protean career orientation - Hou, Liang; Shi, Ruijing; Wang, Zhongji; Zhang, Jun (Frontiers in Psychology, 2025)
Drawing on conservation of resource theory and work-home resources model, this study explores how age-inclusive human resource (HR) practices related to employees’ career sustainability through their work-family enrichment. In line with work-home resource model, we introduce a boundary condition, protean career orientation, to explain when our proposed associated may unfold. We collected data in three waves from 244 employees to test our hypotheses. Results show that age-inclusive HR practices promote employees’ career sustainability through the mediating effect of work-family enrichment. Our findings also emphasize that protean career orientation strengthens the relationship between age-inclusive HR practices and work-family enrichment. Age-inclusive HR practices were more positively linked to career sustainability via work-family enrichment when employees had a high (versus low) protean career orientation. Our research provides a better understanding of how and when age-inclusive HR practices lead to sustainable career.